Application of modular system for innovation buildings architectural design - Kazemi, L. (KNUCA, 2019)
This article deals with the modular regulation techniques in the design of innovative enterprises in order to improve operational efficiency, as well as creating a more rational method of expansion and transformation. Consequently, the advantages of modular architecture in reducing the cost, labor and costs of building materials are compared with traditional methods. In addition, the contribution of further expansion of buildings by modular architecture is described. Based on scientific research, two classes of a modular system are defined for regulating the architectural structure of existing and new objects of an innovative enterprise: combined and specialized. Such systems are realized in the form of a grid, cellular structure and prefabricated units, which allow combining homogeneous and heterogeneous functional zones. At the same time, more acceptable module dimensions are determined for the main types of spaces in innovative enterprises: office, laboratory and production. The use of one or another type of modular solution, which adapts to the requirements of the terrain and the functional process of innovative buildings for various purposes, is recommended. Modular unit techniques for the construction of temporary, permanent and mobile buildings of innovative enterprises are also presented in this article. Prefabricated modules, which include flat materials and spatial blocks, are considered. Metal, wood, plastic and reinforced concrete wrapped and blocks for creating modular systems are the subjects of study in this article. Also, some companies that have developed typical modular buildings from similar building materials are named. The methods of connecting and assembling elements from the modules both at the plant and at the construction site are analyzed. It also explains the relationship between the dimensions of modular structures and vehicles. Examples from world experience are given for each of these types.
Применение модульной системы в проектировании инновационных зданий
Keywords: Science Park; modular system; universality; flexibility; functional area; functional cell